Symbolic Model Checking and Safety Assessment of Altarica models - Bozzano, Marco; Cimatti, Alessandro; Lisagor, Oleg; Mattarei, Cristian; Mover, Sergio; Roveri, Marco; Tonetta, Stefano (Electronic Communications of the EASST, 2012)
Altarica is a language used to describe critical systems. In this paper we present a novel approach to the analysis of Altarica models, based on a translation into an extended version of NuSMV. This approach opens up the possibility to carry out functional verification and safety assessment with symbolic techniques. An experimental evaluation on a set of industrial case studies demonstrates the advantages of the approach over currently available tools.